Sulfoxide-mediated approach to flavones through one-pot Knoevenagel condensation/oxa-Michael addition/sulfoxide elimination process of β-(o-hydroxyaryl)-ketosulfone with arylaldehydes. (17th February 2023) - Tang, Mei-Lin; Ning, Jin-Feng; Li, Yu-Hui; Zhang, Heyanhao; Liu, Mi; Dong, Ye-Jun; Chang, Jun
Graphical abstract: Abstract: In this paper, an easy-operational, high-yielding method for the gram-scale synthesis of flavones is described by a one-pot straightforward sulfoxide-mediated Knoevenagel condensation/intermolecular oxa-Michael annulation/sulfoxide elimination process of β-(o-hydroxyaryl)-ketosulfones (dual nucleophile) and arylaldehydes (dual electrophile). The expeditious synthetic route sets up flavones, including the bond formation of one CO and one double CC bonds via a formal (5 + 1) cycloaddition. Furthermore, among them, compounds 7bn could be an excellent starting point for further development of drugs to benefit the field of anti-aging.